Data retention ability of PVDF-TrFE as organic ferroelectric field-effect transistors - Yap, Wei Hao (2014)
In this project, retention ability of PVDF – TrFE ferroelectric field effect transistors which utilizes either air stable PCDTBT or non-stable regioregular (rr) – P3HT as the semiconducting polymer are investigated in both air and inert environment over a period of 7 days. Field effect transistors using rr-P3HT and PCDTBT as semiconducting polymer and Cytop as the dielectric material are also investigated to understand their suitability for use in organic devices. Devices are fabricated by spin coating semiconducting material and dielectric layer followed by annealing process before evaporative deposition of gold gate metal to construct top gate bottom contact field effect transistors. Characterization techniques employed involves gate sweep and drain sweep where transfer and output characteristics of the fabricated devices are measured.